Preparation method of carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance

By preparing banana peels into carbon nanotubes/silver doped biomass carbon materials, the problems of high cost and environmental pollution of existing carbon-based electromagnetic shielding materials are solved, and low-cost, environmentally friendly electromagnetic shielding materials are achieved, with excellent Electromagnetic shielding performance and lightweight properties, suitable for multiple fields.

CN119263258AActive Publication Date: 2025-01-07HEFEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411390279.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing carbon-based electromagnetic shielding composite materials have high cost, high quality and difficult processing. The use of strong oxidants during the modification process leads to environmental pollution, making it difficult to apply to the lightweight materials field on a large scale, and do not meet the requirements of green and environmental protection.

Method used

Using carbon nanotubes/silver doped biomass carbon material, the banana peel is used as the biomass material, and through hydrothermal pre-carbonization, freeze-drying, high-temperature carbonization and ultrasonic mixing, it forms a multi-level multi-layer pore structure. Carbon nanotubes/silver doped biomass carbon materials significantly improve electromagnetic shielding efficiency and reduce environmental pollution.

Benefits of technology

It realizes low-cost and environmentally friendly electromagnetic shielding material preparation, with good electromagnetic shielding performance, lightweight characteristics and stability. It is suitable for electronics, automobiles, aerospace and other fields, effectively suppresses electromagnetic interference and ensures the stability and safety of equipment. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263258A_ABST
    Figure CN119263258A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance, and belongs to the field of electromagnetic shielding materials. The carbon nano tube / silver doped biomass carbon material is prepared from the following raw materials in parts by weight: 18 to 22 parts of banana peel, 0.05 to 0.2 part of silver nitrate, 0.08 to 0.12 part of carbon nano tube and 1 to 1.5 parts of pore forming agent. Through scientific material selection and raw material treatment, the electromagnetic shielding effectiveness is effectively improved, forming processing is easy, the environmental protection requirement is met, national development of circular economy is facilitated, efficient utilization of resources is achieved, and strategic deployment of reduction, reutilization and recycling of waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic shielding materials, and in particular relates to a method for preparing a carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance. Background Art

[0002] With the advent of the information age and the continuous development of science and technology, the development and popularization of electronic products and equipment such as smart phones, electric vehicles and smart home appliances is a double-edged sword. On the one hand, it has brought great convenience to people's lives, but on the other hand, it has also brought electromagnetic radiation pollution, affecting people's lives.

[0003] At present, carbon-based shielding composite materials mainly add graphene and carbon nanotube composite fillers to the matrix, and achieve electromagnetic shielding effectiveness by virtue of their excellent conductivity and electromagnetic shielding effectiveness, as well as good synergistic effect. However, such materials are expensive and heavy, making processing difficult. This makes them difficult to apply on a large scale in areas that require lightweight materials. In addition, some modification processes use strong oxidants, which will cause environmental pollution and are not in line with the concept of green environmental protection. Summary of the invention

[0004] The present invention aims at the deficiencies of the above-mentioned prior art and provides a method for preparing a carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance. The present invention effectively improves the electromagnetic shielding effectiveness through scientific material selection and the process flow of raw material processing, is easy to shape and process, meets environmental protection requirements, and is conducive to the development of the country's circular economy, the efficient utilization of resources and the strategic deployment of waste reduction, reuse and resource utilization.

[0005] The method for preparing the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance of the present invention comprises the following steps:

[0006] Step 1: Preprocessing

[0007] Cut the banana peel into small pieces, add them into acetone solution, and treat them ultrasonically for 20-40 minutes; immerse the treated banana peel in deionized water and continue to treat it ultrasonically for 10-30 minutes.

[0008] Step 2: Hydrothermal Pre-carbonization

[0009] The pretreated banana peel is placed in a polytetrafluoroethylene-lined hydrothermal reactor, and a porogen aqueous solution is added. After mixing evenly, the mixture is hydrothermally pre-carbonized at 170-190°C for 11-13 hours. After the reaction is completed, the solution is removed to obtain a gel-like banana peel, which is then placed in an oven and dried at 50-70°C for 1-3 hours.

[0010] Step 3: Freeze Drying

[0011] Add silver nitrate solution to the sample obtained in step 2, perform ultrasonic treatment for 20-40 minutes, take it out and freeze it at -75°C to -70°C for 7-9 hours, then place it in a freeze dryer drying rack for vacuum drying to obtain biomass aerogel.

[0012] Step 4: High temperature carbonization

[0013] The biomass aerogel obtained in step 3 is placed in a tubular furnace and subjected to high-temperature carbonization treatment in a nitrogen atmosphere to obtain silver-doped biomass carbon aerogel.

[0014] Step 5: Ultrasonic mixing

[0015] Weigh 0.08-0.12 parts of carbon nanotubes, add them to 20-40 mL of acetone solution to obtain a carbon nanotube-acetone solution; grind and crush the silver-doped biomass carbon aerogel obtained in step 4, add it to the carbon nanotube-acetone solution, and perform ultrasonic mixing for 60-100 minutes.

[0016] Step 6: Vacuum Drying

[0017] The sample obtained in step 5 is placed in a freeze dryer drying rack for vacuum drying to obtain a carbon nanotube / silver-doped biomass carbon material.

[0018] In step 1, after cutting the banana peel into pieces, control the size of each piece to 1 cm (length) × 1 cm (width) × 0.3 cm (thickness).

[0019] In step 2, the porogen aqueous solution is prepared by dissolving 1-1.5 parts of porogen in 20-30 parts of water.

[0020] In step 3, the silver nitrate solution is prepared by dissolving 0.05-0.2 parts of silver nitrate solid particles in 8-10 mL of water.

[0021] In step 3, the parameters of the vacuum drying process are set as follows: the chamber vacuum is controlled to be 2-5 Pa, the cold trap temperature is -75°C to -70°C, the sample temperature is -60°C to -50°C, and the vacuum drying time is 14-16h.

[0022] In step 4, the parameters of the high temperature carbonization treatment are set as follows: start heating at 40-60°C, with a heating rate of 2-3°C / min, keep warm at 440-450°C for 100-140min, then continue heating to 680-720°C at a heating rate of 2-3°C / min, and keep warm for 120-180min.

[0023] In step 6, the parameters of the vacuum drying process are set as follows: the chamber vacuum is controlled to 2-5 Pa, the cold trap temperature is set to -75°C to -70°C, the sample temperature is -60°C to -50°C, and the vacuum drying time is 14-16h.

[0024] During the preparation process, the raw materials are composed of the following by mass:

[0025] 18-22 parts of banana peel, 0.05-0.2 parts of silver nitrate, 0.08-0.12 parts of carbon nanotubes, and 1-1.5 parts of pore-forming agent.

[0026] The pore-forming agent is one of potassium hydroxide or sodium hydroxide.

[0027] First, banana peel, as a biomass material, can be converted into activated carbon with a porous structure and a high specific surface area and rich pore structure through hydrothermal carbonization treatment. Next, the addition of metal elements can significantly improve the conductivity and electromagnetic properties of the material. Metals are good conductors and can effectively absorb and reflect electromagnetic waves. Adding metals during the carbonization process of banana peels can form metal-carbon composite materials, which have potential application value in the field of electromagnetic shielding. Furthermore, coating carbon nanotubes (CNTs) on the surface of the metal-carbon composite material can further enhance its electromagnetic shielding performance. Carbon nanotubes are widely used in electromagnetic shielding, conductive materials and other fields due to their unique structure and excellent electrical and mechanical properties. The high aspect ratio and conductivity of carbon nanotubes enable them to effectively absorb and scatter electromagnetic waves, thereby enhancing the electromagnetic shielding effect of the material.

[0028] The carbon nanotube / silver-doped biomass carbon material of the present invention can effectively suppress electromagnetic interference, has the characteristics of low density and high porosity, can significantly reduce the weight of the structure, and maintain good mechanical properties and stability. At the same time, it has the advantage of environmental protection, wherein the natural biomass material is used as a precursor, which is not only low-cost and abundant in source, but also has less environmental pollution during the preparation process, which meets the requirements of green development; in addition, since it has a multi-level and multi-layered pore structure, this complex pore structure helps to extend the propagation path of electromagnetic waves, and effectively converts electromagnetic wave energy into heat energy through multiple reflections, interface polarization, conduction loss and dipole polarization mechanisms, thereby achieving an efficient shielding effect, and can be used in the fields of electronics, automobiles, aerospace and communications, effectively suppressing electromagnetic interference and ensuring the stability and safety of electronic equipment.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] The present invention provides a method for preparing a carbon nanotube / silver-doped biomass carbon material with good electromagnetic shielding performance. As a filler of a shielding material, the synthetic product is light in weight and has a wide source of raw materials. In addition, due to its multi-level and multi-layered pore structure, it helps to extend the propagation path of electromagnetic waves and achieves efficient shielding effect through multiple reflections, interface polarization and other mechanisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a graph showing the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 1 as a function of frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -28.51 dB to -33.99 dB, which has a good electromagnetic shielding effect.

[0032] Figure 2 This is a graph showing the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 2 as a function of frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -21.37 dB to -25.87 dB, which has a good electromagnetic shielding effect.

[0033] Figure 3 This is a graph showing how the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 3 varies with frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -38.14 dB to -42.35 dB, which can shield more than 99% of electromagnetic waves and has a relatively excellent electromagnetic shielding effect.

[0034] Figure 4 This is a graph showing how the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 4 varies with frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -22.59 dB to -28.39 dB, and the electromagnetic shielding effectiveness is above 20 dB, which can shield 99% of electromagnetic waves, and the electromagnetic shielding effect is relatively good.

[0035] Figure 5 This is a microscopic characterization image of the carbon nanotube / silver-doped biomass carbon material prepared in Example 4 under a scanning electron microscope. Figure 5 It can be seen that the prepared material has an obvious pore structure, low density and light weight. This pore structure helps to extend the propagation path of electromagnetic waves and effectively convert electromagnetic wave energy into heat energy through mechanisms such as multiple reflections, thereby achieving an efficient shielding effect. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0037] Embodiment 1:

[0038] The raw materials of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment include, by weight: 20 parts of banana peels, 0.064 parts of silver nitrate particles, 0.1 parts of carbon nanotubes, and 1 part of a pore-forming agent.

[0039] The banana peel is cut into pieces, each piece having a size of 1 cm (length)×1 cm (width)×0.3 cm (thickness).

[0040] The pore-forming agent is potassium hydroxide.

[0041] The preparation process of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment is as follows:

[0042] (1) Pretreatment

[0043] Weigh 20 portions of banana peels and cut them into small pieces, each piece is 1 cm (length) × 1 cm (width) × 0.3 cm (thickness), put the cut banana peels in a beaker, prepare 70 ml of banana peel-acetone mixed solution, and ultrasonically treat for 30 minutes; immerse the treated banana peels in deionized water, prepare 70 ml of banana peel-deionized water mixed solution, and then ultrasonically treat for 20 minutes.

[0044] (2) Hydrothermal precarbonization treatment

[0045] The banana peel pretreated in step (1) is placed in a polytetrafluoroethylene-lined hydrothermal reactor, and 1 part of potassium hydroxide is dissolved in 20 parts of water and stirred to prepare a potassium hydroxide aqueous solution, the pore-forming agent aqueous solution is mixed with the banana peel, and a hydrothermal pre-carbonization treatment is performed at a temperature of 180° C. for 12 hours; then the solution is poured off to obtain a gel-like banana peel after hydrothermal treatment with the potassium hydroxide aqueous solution, and the gel-like banana peel is placed in an oven and dried at 60° C. for 2 hours.

[0046] (3) Freeze-drying

[0047] a. Weigh 0.064 parts of silver nitrate particles and dissolve them in 10 ml of water to prepare a silver nitrate solution. After stirring for 2 min, add the sample prepared in step (2) and perform ultrasonic treatment for 30 min.

[0048] b. Freeze the sample obtained in a at -74.5°C for 8 h.

[0049] c. Place the frozen sample in a freeze dryer drying rack for vacuum drying, control the chamber vacuum to 2Pa, the cold trap temperature to -74°C, the sample temperature to -56°C, and the vacuum drying time to 15h to obtain biomass aerogel.

[0050] (4) High temperature carbonization treatment

[0051] The biomass aerogel obtained in step (3) is placed in a tubular furnace for high-temperature carbonization treatment in a nitrogen atmosphere, and the carbonization temperature is: starting from 50°C, heating at a heating rate of 2°C / min, keeping at 450°C for 120min, and then continuing to heat to 700°C at a heating rate of 2°C / min, and keeping for 150min; obtaining silver-doped biomass carbon aerogel.

[0052] (5) Ultrasonic mixing treatment

[0053] a. Weigh 0.1 parts of carbon nanotubes and add them to 30 ml of acetone solution to obtain a carbon nanotube-acetone solution.

[0054] b. Grind and crush the silver-doped biomass carbon aerogel obtained in (4) and place it in the carbon nanotube-acetone solution obtained in a, and perform ultrasonic mixing treatment for 80 minutes.

[0055] (6) Vacuum drying

[0056] The sample obtained in step (5) is placed in a freeze dryer drying rack for vacuum drying for 15 hours, wherein the chamber vacuum is set to 2Pa, the cold trap temperature is set to -74°C, and the sample temperature is -57.4°C. Mechanically cross-linked carbon nanotubes are produced during the low-temperature vacuum drying process, and the silver-doped biomass carbon is fixed therein to obtain carbon nanotube / silver-doped biomass carbon material.

[0057] The electromagnetic shielding performance of the carbon nanotube / silver-doped biomass carbon material prepared above was tested by a vector network analyzer using a coaxial method, and it was found that its electromagnetic shielding performance in the Ku band (12-18 GHz) was -28.51 dB to -33.99 dB.

[0058] Embodiment 2:

[0059] The raw materials of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment include, by weight: 20 parts of banana peels, 0.064 parts of silver nitrate particles, 0.1 parts of carbon nanotubes, and 1 part of a pore-forming agent.

[0060] The banana peel is cut into pieces, each piece having a size of 1 cm (length)×1 cm (width)×0.3 cm (thickness).

[0061] The pore-forming agent is sodium hydroxide.

[0062] The preparation process of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment is as follows:

[0063] (1) Pretreatment

[0064] Weigh 20 portions of banana peels and cut them into small pieces, each piece is 1 cm (length) × 1 cm (width) × 0.3 cm (thickness), put the cut banana peels in a beaker, prepare 70 ml of banana peel-acetone mixed solution, and ultrasonically treat for 30 minutes; immerse the treated banana peels in deionized water, prepare 70 ml of banana peel-deionized water mixed solution, and then ultrasonically treat for 20 minutes.

[0065] (2) Hydrothermal precarbonization treatment

[0066] The banana peel pretreated in step (1) is placed in a polytetrafluoroethylene-lined hydrothermal reactor, and 1 part of sodium hydroxide is dissolved in 20 parts of water and stirred to prepare a sodium hydroxide aqueous solution, the pore-forming agent aqueous solution is mixed with the banana peel, and a hydrothermal pre-carbonization treatment is performed at a temperature of 180° C. for 12 hours; then the solution is poured off to obtain a gel-like banana peel after hydrothermal treatment with the sodium hydroxide aqueous solution, and the gel-like banana peel is placed in an oven and dried at 60° C. for 2 hours.

[0067] (3) Freeze-drying

[0068] a. Weigh 0.064 parts of silver nitrate particles and dissolve them in 10 ml of water to prepare a silver nitrate solution. After stirring for 2 min, add the sample prepared in step (2) and perform ultrasonic treatment for 30 min.

[0069] b. Freeze the sample obtained in a at -74.5°C for 8 h.

[0070] c. Place the frozen sample in a freeze dryer drying rack for vacuum drying, control the chamber vacuum to 2Pa, the cold trap temperature to -74°C, the sample temperature to -56°C, and the vacuum drying time to 15h to obtain biomass aerogel.

[0071] (4) High temperature carbonization treatment

[0072] The biomass aerogel obtained in step (3) is placed in a tubular furnace for high-temperature carbonization treatment in a nitrogen atmosphere, and the carbonization temperature is: starting from 50°C, heating at a heating rate of 2°C / min, keeping at 450°C for 120min, and then continuing to heat to 700°C at a heating rate of 2°C / min, and keeping for 150min; obtaining silver-doped biomass carbon aerogel.

[0073] (5) Ultrasonic mixing treatment

[0074] a. Weigh 0.1 parts of carbon nanotubes and add them to 30 ml of acetone solution to obtain a carbon nanotube-acetone solution.

[0075] b. Grind and crush the silver-doped biomass carbon aerogel obtained in (4) and place it in the carbon nanotube-acetone solution obtained in a, and perform ultrasonic mixing treatment for 80 minutes.

[0076] (6) Vacuum drying

[0077] The sample obtained in step (5) is placed in a freeze dryer drying rack for vacuum drying for 15 hours, wherein the chamber vacuum is set to 2Pa, the cold trap temperature is set to -74°C, and the sample temperature is -57.4°C. Mechanically cross-linked carbon nanotubes are produced during the low-temperature vacuum drying process, and the silver-doped biomass carbon is fixed therein to obtain carbon nanotube / silver-doped biomass carbon material.

[0078] The electromagnetic shielding performance of the carbon nanotube / silver-doped biomass carbon material prepared above was tested by a vector network analyzer through a coaxial method, and it was found that its electromagnetic shielding performance in the Ku band (12-18 GHz) was -21.37 dB to -25.87 dB.

[0079] Embodiment 3:

[0080] The raw materials of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment include, by weight: 20 parts of banana peels, 0.128 parts of silver nitrate particles, 0.1 parts of carbon nanotubes, and 1 part of a pore-forming agent.

[0081] The banana peel is cut into pieces, each piece having a size of 1 cm (length)×1 cm (width)×0.3 cm (thickness).

[0082] The pore-forming agent is potassium hydroxide.

[0083] The preparation process of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment is as follows:

[0084] (1) Pretreatment

[0085] Weigh 20 portions of banana peels and cut them into small pieces, each piece is 1 cm (length) × 1 cm (width) × 0.3 cm (thickness), put the cut banana peels in a beaker, prepare 70 ml of banana peel-acetone mixed solution, and ultrasonically treat for 30 minutes; immerse the treated banana peels in deionized water, prepare 70 ml of banana peel-deionized water mixed solution, and then ultrasonically treat for 20 minutes.

[0086] (2) Hydrothermal precarbonization treatment

[0087] The banana peel pretreated in step (1) is placed in a polytetrafluoroethylene-lined hydrothermal reactor, and 1 part of potassium hydroxide is dissolved in 20 parts of water and stirred to prepare a potassium hydroxide aqueous solution, the pore-forming agent aqueous solution is mixed with the banana peel, and a hydrothermal pre-carbonization treatment is performed at a temperature of 180° C. for 12 hours; then the solution is poured off to obtain a gel-like banana peel after hydrothermal treatment with the potassium hydroxide aqueous solution, and the gel-like banana peel is placed in an oven and dried at 60° C. for 2 hours.

[0088] (3) Freeze-drying

[0089] a. Weigh 0.128 parts of silver nitrate particles and dissolve them in 10 ml of water to prepare a silver nitrate solution. After stirring for 2 min, add the sample prepared in step (2) and perform ultrasonic treatment for 30 min.

[0090] b. Freeze the sample obtained in a at -74.5°C for 8 h.

[0091] c. Place the frozen sample in a freeze dryer drying rack for vacuum drying, control the chamber vacuum to 2Pa, the cold trap temperature to -74°C, the sample temperature to -56°C, and the vacuum drying time to 15h to obtain biomass aerogel.

[0092] (4) High temperature carbonization treatment

[0093] The biomass aerogel obtained in step (3) is placed in a tubular furnace for high-temperature carbonization treatment in a nitrogen atmosphere, and the carbonization temperature is: starting from 50°C, heating at a heating rate of 2°C / min, keeping at 450°C for 120min, and then continuing to heat to 700°C at a heating rate of 2°C / min, and keeping for 150min; obtaining silver-doped biomass carbon aerogel.

[0094] (5) Ultrasonic mixing treatment

[0095] a. Weigh 0.1 parts of carbon nanotubes and add them to 30 ml of acetone solution to obtain a carbon nanotube-acetone solution.

[0096] b. Grind and crush the silver-doped biomass carbon aerogel obtained in (4) and place it in the carbon nanotube-acetone solution obtained in a, and perform ultrasonic mixing treatment for 80 minutes.

[0097] (6) Vacuum drying

[0098] The sample obtained in step (5) is placed in a freeze dryer drying rack for vacuum drying for 15 hours, wherein the chamber vacuum is set to 2Pa, the cold trap temperature is set to -74°C, and the sample temperature is -57.4°C. Mechanically cross-linked carbon nanotubes are produced during the low-temperature vacuum drying process, and the silver-doped biomass carbon is fixed therein to obtain carbon nanotube / silver-doped biomass carbon material.

[0099] The electromagnetic shielding performance of the carbon nanotube / silver-doped biomass carbon material prepared above was tested by a vector network analyzer through a coaxial method, and it was found that its electromagnetic shielding performance in the Ku band (12-18 GHz) was -38.14 dB to -42.35 dB.

[0100] Embodiment 4:

[0101] The raw materials of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment include, by weight: 20 parts of banana peels, 0.128 parts of silver nitrate particles, 0.1 parts of carbon nanotubes, and 1 part of a pore-forming agent.

[0102] The banana peel is cut into pieces, each piece having a size of 1 cm (length)×1 cm (width)×0.3 cm (thickness).

[0103] The pore-forming agent is sodium hydroxide.

[0104] The preparation process of the carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance in this embodiment is as follows:

[0105] (1) Pretreatment

[0106] Weigh 20 portions of banana peels and cut them into small pieces, each piece is 1 cm (length) × 1 cm (width) × 0.3 cm (thickness), put the cut banana peels in a beaker, prepare 70 ml of banana peel-acetone mixed solution, and ultrasonically treat for 30 minutes; immerse the treated banana peels in deionized water, prepare 70 ml of banana peel-deionized water mixed solution, and then ultrasonically treat for 20 minutes.

[0107] (2) Hydrothermal precarbonization treatment

[0108] The banana peel pretreated in step (1) is placed in a polytetrafluoroethylene-lined hydrothermal reactor, and 1 part of sodium hydroxide is dissolved in 20 parts of water and stirred to prepare a sodium hydroxide aqueous solution, the pore-forming agent aqueous solution is mixed with the banana peel, and a hydrothermal pre-carbonization treatment is performed at a temperature of 180° C. for 12 hours; then the solution is poured off to obtain a gel-like banana peel after hydrothermal treatment with the sodium hydroxide aqueous solution, and the gel-like banana peel is placed in an oven and dried at 60° C. for 2 hours.

[0109] (3) Freeze-drying

[0110] a. Weigh 0.128 parts of silver nitrate particles and dissolve them in 10 ml of water to prepare a silver nitrate solution. After stirring for 2 min, add the sample prepared in step (2) and perform ultrasonic treatment for 30 min.

[0111] b. Freeze the sample obtained in a at -74.5°C for 8 h.

[0112] c. Place the frozen sample in a freeze dryer drying rack for vacuum drying, control the chamber vacuum to 2Pa, the cold trap temperature to -74°C, the sample temperature to -56°C, and the vacuum drying time to 15h to obtain biomass aerogel.

[0113] (4) High temperature carbonization treatment

[0114] The biomass aerogel obtained in step (3) is placed in a tubular furnace for high-temperature carbonization treatment in a nitrogen atmosphere, and the carbonization temperature is: starting from 50°C, heating at a heating rate of 2°C / min, keeping at 450°C for 120min, and then continuing to heat to 700°C at a heating rate of 2°C / min, and keeping for 150min; obtaining silver-doped biomass carbon aerogel.

[0115] (5) Ultrasonic mixing treatment

[0116] a. Weigh 0.1 parts of carbon nanotubes and add them to 30 ml of acetone solution to obtain a carbon nanotube-acetone solution.

[0117] b. Grind and crush the silver-doped biomass carbon aerogel obtained in (4) and place it in the carbon nanotube-acetone solution obtained in a, and perform ultrasonic mixing treatment for 80 minutes.

[0118] (6) Vacuum drying

[0119] The sample obtained in step (5) is placed in a freeze dryer drying rack for vacuum drying for 15 hours, wherein the chamber vacuum is set to 2Pa, the cold trap temperature is set to -74°C, and the sample temperature is -57.4°C. Mechanically cross-linked carbon nanotubes are produced during the low-temperature vacuum drying process, and the silver-doped biomass carbon is fixed therein to obtain carbon nanotube / silver-doped biomass carbon material.

[0120] The electromagnetic shielding performance of the carbon nanotube / silver-doped biomass carbon material prepared above was tested by a vector network analyzer through a coaxial method, and the electromagnetic shielding performance in the Ku band (12-18 GHz) was measured to be -22.59 dB to -28.39 dB.

[0121] The electromagnetic shielding performance of the materials prepared in each embodiment was tested and analyzed on the obtained samples in the Ku band (12-18 GHz) using a vector network analyzer.

[0122] Figure 1 This is a graph showing the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 1 as a function of frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -28.51 dB to -33.99 dB, which has a good electromagnetic shielding effect.

[0123] Figure 2 This is a graph showing the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 2 as a function of frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -21.37 dB to -25.87 dB, which has a good electromagnetic shielding effect.

[0124] Figure 3 This is a graph showing how the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 3 varies with frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -38.14 dB to -42.35 dB, which can shield more than 99% of electromagnetic waves and has a relatively excellent electromagnetic shielding effect.

[0125] Figure 4 This is a graph showing how the electromagnetic shielding effectiveness of the carbon nanotube / silver-doped biomass carbon material prepared in Example 4 varies with frequency. It can be seen from the graph that within the Ku band (12-18 GHz) frequency range, the electromagnetic shielding effectiveness of the composite material is -22.59 dB to -28.39 dB, and the electromagnetic shielding effectiveness is above 20 dB, which can shield 99% of electromagnetic waves, and the electromagnetic shielding effect is relatively good.

[0126] Figure 5 This is a microscopic characterization image of the carbon nanotube / silver-doped biomass carbon material prepared in Example 4 under a scanning electron microscope. Figure 5 It can be seen that the prepared material has an obvious pore structure, low density and light weight. This pore structure helps to extend the propagation path of electromagnetic waves and effectively convert electromagnetic wave energy into heat energy through mechanisms such as multiple reflections, thereby achieving an efficient shielding effect.

[0127] In order to compare the effects of the present invention, the above-mentioned groups of embodiments were subjected to performance tests, and the specific comparative data are shown in the following Table 1:

[0128] Table 1

[0129]

[0130] Observe the performance curves of Example 1 and Example 3, where the shielding performance of Example 1 in the Ku band (12-18GHz) is -28.51dB to -33.99dB, and the shielding performance of Example 3 in the Ku band (12-18GHz) is -38.14dB to -42.35dB. It can be seen that when the pore-forming agent is potassium hydroxide, the shielding effectiveness is significantly improved with the increase of the amount of silver nitrate added. Observe the performance curves of Example 2 and Example 4, where the shielding performance of Example 2 in the Ku band (12-18GHz) is -21.37dB to -25.87dB, and the shielding performance of Example 4 in the Ku band (12-18GHz) is -22.59dB to -28.39dB. It can be seen that when the pore-forming agent is sodium hydroxide, the shielding effectiveness is significantly improved with the increase of the amount of silver nitrate added. At the same time, it can be seen from Table 1 and the performance diagram that in this experimental process, when the amount of silver nitrate added is the same, the sample obtained when the pore-forming agent is potassium hydroxide has better shielding performance than the sample obtained when the pore-forming agent is sodium hydroxide.

[0131] From the above, it can be seen that the carbon nanotube / silver-doped biomass carbon material prepared by the method of the present invention has good performance, meets environmental protection requirements, realizes efficient utilization of resources and reduction of waste and lightweight design of products, and provides a new technical solution for the selection of preparation of electromagnetic shielding material fillers.

Claims

1. A method for preparing a carbon nanotube / silver-doped biomass carbon material with electromagnetic shielding performance, characterized in that The steps include: Step 1: Preprocessing Cut 18-22 portions of banana peel into small pieces, add them to an acetone solution, and ultrasonically treat them for 20-40 minutes; immerse the treated banana peels in deionized water and continue ultrasonically treating them for 10-30 minutes; Step 2: Hydrothermal Pre-carbonization The pretreated banana peel is placed in a polytetrafluoroethylene-lined hydrothermal reactor, a porogen aqueous solution is added, and the mixture is mixed evenly before hydrothermal pre-carbonization treatment is performed; after the reaction is completed, the solution is removed to obtain a gel-like banana peel, which is then placed in an oven for drying; Step 3: Freeze Drying Add silver nitrate solution to the sample obtained in step 2, perform ultrasonic treatment for 20-40 minutes, take it out and freeze it at -75°C to -70°C for 7-9 hours, then place it in a freeze dryer drying rack for vacuum drying to obtain biomass aerogel; Step 4: High temperature carbonization The biomass aerogel obtained in step 3 is placed in a tubular furnace and subjected to high-temperature carbonization treatment in a nitrogen atmosphere to obtain a silver-doped biomass carbon aerogel; Step 5: Ultrasonic mixing Weigh 0.08-0.12 parts of carbon nanotubes and add them to acetone to obtain a carbon nanotube-acetone solution; grind and crush the silver-doped biomass carbon aerogel obtained in step 4, add it to the carbon nanotube-acetone solution, and perform ultrasonic mixing for 60-100 minutes; Step 6: Vacuum Drying The sample obtained in step 5 is placed in a freeze dryer drying rack for vacuum drying to obtain a carbon nanotube / silver-doped biomass carbon material.

2. The preparation method according to claim 1, characterized in that: In step 2, the porogen aqueous solution is prepared by dissolving 1-1.5 parts of porogen in 20-30 parts of water.

3. The preparation method according to claim 2, characterized in that: The pore-forming agent is one of potassium hydroxide or sodium hydroxide.

4. The preparation method according to claim 1, characterized in that: In step 2, the temperature of the hydrothermal pre-carbonization treatment is 170-190° C. and the time is 11-13 hours.

5. The preparation method according to claim 1, characterized in that: In step 3, the silver nitrate solution is prepared by dissolving 0.05-0.2 parts of silver nitrate solid particles in 8-10 mL of water.

6. The preparation method according to claim 1, characterized in that: In step 3, the parameters of the vacuum drying process are set as follows: the chamber vacuum is controlled to be 2-5 Pa, the cold trap temperature is -75°C to -70°C, the sample temperature is -60°C to -50°C, and the vacuum drying time is 14-16h.

7. The preparation method according to claim 1, characterized in that: In step 4, the parameters of the high temperature carbonization treatment are set as follows: start heating at 40-60°C, with a heating rate of 2-3°C / min, keep warm at 440-450°C for 100-140min, then continue heating to 680-720°C at a heating rate of 2-3°C / min, and keep warm for 120-180min.

8. The preparation method according to claim 1, characterized in that: In step 6, the parameters of the vacuum drying process are set as follows: the chamber vacuum is controlled to 2-5 Pa, the cold trap temperature is set to -75°C to -70°C, the sample temperature is -60°C to -50°C, and the vacuum drying time is 14-16h.

Citation Information

Patent Citations

  • Foam metal copper mingled carbon nanometer tube electromagnetic shield material and preparation method

    CN109898107A

  • Preparation method of conductive wood aerogel

    CN113119256A

  • Carbon nanotube composite material electromagnetic shielding film and preparation method thereof

    CN113698639A

  • Preparation method of biomass carbon / silver composite electromagnetic shielding material and biomass carbon / silver composite electromagnetic shielding material

    CN118419900A

  • Anisotropic heat transfer, electromagnetic interference shielding composite and method for preparation thereof

    US20220132709A1